The Influence of Transformational Leadership and Work Environment on Employee Performance Mediated by Motivation at PT HJS - Jeni Jeni; Fahrul Riza; Liem Bambang Sugiyanto; Bisma Jatmika Tisnasasmita (Eduvest - Journal of Universal Studies, 2026)
Project-oriented company possess unique characteristics including high work dynamics and uncertainty that require different approaches in understanding employee performance determinants. This study aims to analyze how transformational leadership and workplace environment contribute to employee performance, while also investigating the mediating role of work motivation among employees at PT HJS, a construction and industrial estate development company in Batam, Indonesia. This study employed a quantitative explanatory approach using a census sampling technique involving 100 employees from five operational divisions. Data were collected through structured questionnaires using a 5-point Likert scale and analyzed using SEM-PLS through SmartPLS 4.0. Mediation testing was conducted using specific indirect effects analysis. The findings revealed that transformational leadership (β = 0.158; p = 0.263) and work environment (β = 0.008; p = 0.962) had no significant direct effect on employee performance. However, both factors significantly enhanced work motivation (TL → WM: β = 0.431; p < 0.001; WE → WM: β = 0.443; p < 0.001), which subsequently improved employee performance (WM → EP: β = 0.388; p = 0.013). Mediation analysis confirmed that work motivation fully mediated the relationship between work environment and employee performance and mediated the relationship between transformational leadership and employee performance. These findings enrich Organizational Behavior literature by demonstrating that in project-oriented company contexts, the influence of organizational factors on performance is entirely transmitted through motivational processes, differing from findings in conventional organizations. Practically, management is advised to prioritize motivation enhancement programs as the primary strategy for improving performance of employee.